2019
DOI: 10.1177/0093650219841736
|View full text |Cite
|
Sign up to set email alerts
|

Deceptive Affection Across Relational Contexts: A Group Comparison of Romantic Relationships, Cross-Sex Friendships, and Friends With Benefits Relationships

Abstract: Communicating affection is important for developing and maintaining relationships; yet, it can be risky when it is used deceptively. Grounded in affection exchange theory (AET), the purpose of the present study is to test how types of deceptive affection—or incongruity between affection felt and expressed—predicts relational health differently across three relational contexts: romantic relationships (RRs), cross-sex friendships (CSFs), and friends with benefits relationships (FWBRs). Multiple group analyses us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In one review, Floyd and Pauley (2011) summarized several risks associated with affectionate communication, including nonreciprocity and social censure. Trask, Horstman, and Hesse (2016) found an inverse correlation between deintensified affection (a type of deceptive affection) and relational health for individual within friends-with-benefits relationships. These ideas move toward an analysis of the effects of affection deprivation on individual and relational well-being.…”
mentioning
confidence: 95%
“…In one review, Floyd and Pauley (2011) summarized several risks associated with affectionate communication, including nonreciprocity and social censure. Trask, Horstman, and Hesse (2016) found an inverse correlation between deintensified affection (a type of deceptive affection) and relational health for individual within friends-with-benefits relationships. These ideas move toward an analysis of the effects of affection deprivation on individual and relational well-being.…”
mentioning
confidence: 95%
“…Negative relationships, though, among general deception and commitment and satisfaction were revealed. Adding understanding to Gillen et al’s findings, Trask et al (2020) found differences in the communication of intensified affection based on relationship type, with higher levels of this DAM form in friends with benefits relationships compared to cross-sex friendships and romantic relationships. Trask et al further reported positive relationships among intensified affection and relational health, considered to be commitment, satisfaction, and closeness.…”
Section: Introductionmentioning
confidence: 48%
“…However, this seems fairly implausible because participants could decline or ignore the prompts and, indeed, did so regularly. Regardless, research indicates that deceptive affection is associated with relational health, possibly because internal feelings are modified to reflect the enacted behavior (Trask et al, 2016). This modification of feelings might require a high-quality relationship, which was the case in our sample (Online Supplement 1).…”
Section: Discussionmentioning
confidence: 99%